2016
DOI: 10.1002/ppul.23546
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis Score of Sant Joan de Déu: BROSJOD Score, validation and usefulness

Abstract: There is a high inter-rater reliability, showing the BROSJOD score to be reliable and valid, even when different observers apply it. Pediatr Pulmonol. 2017;52:533-539. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 34 publications
0
46
0
1
Order By: Relevance
“…In previous studies, bronchiolitis or asthma severity scores have been determined by nurses, respiratory therapists, or by two physicians . Balaguer et al recently attempted to validate the bronchiolitis score of Sant Joan De Deu when used by two physicians. However, the Sant Joan De Deu score is a complex scoring system comprising six parameters with stratification for different age groups, which is difficult for untrained physicians to use.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, bronchiolitis or asthma severity scores have been determined by nurses, respiratory therapists, or by two physicians . Balaguer et al recently attempted to validate the bronchiolitis score of Sant Joan De Deu when used by two physicians. However, the Sant Joan De Deu score is a complex scoring system comprising six parameters with stratification for different age groups, which is difficult for untrained physicians to use.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to follow infants’ clinical evolution more accurately, we strongly recommend registering distress scores daily, because this measure seems to be a good predictor of clinical outcomes, as highlighted by Balaguer et al. ().…”
Section: Discussionmentioning
confidence: 99%
“…The Sant Joan de Déu Bronchiolitis Score (BROSJOD score) was originally developed in 1999 (Balaguer et al., ), and it was recently validated as a diagnostic severity tool in infants aged less than 2 years, mean age 52.5 days, admitted to Hospital Sant Joan de Déu with acute bronchiolitis (Emergency Department, ward, or PICU) (Balaguer et al., ). At admission, the BROSJOD showed good internal consistency (Cronbach's alpha .75 [95% CI: 0.71 to 0.82]), high inter‐rater reliability (Concordance Correlation Coefficient, CCC 0.96 [95% CI: 0.94 to 0.97]) and good discriminative validity (Volume Under Surface, VUS 0.80 [95% CI: 0.70 to 0.90]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute viral bronchiolitis, particularly due to RSV or rhinovirus, is known to be associated with subsequent recurrent wheeze . Balaguer et al found the clinical severity score known as Bronchiolitis Score of Sant Joan de Déu (BROSJOD) to be a reliable indicator of disease severity for acute bronchiolitis between independent observers. Another scoring system, the modified Respiratory Index Score (RIS), was found to be a reasonable predictor of the need for hospital admission in a single‐center study in Singapore .…”
Section: Introductionmentioning
confidence: 99%